Indigenous tree uses, use-values and impact of human population on forest size, structure and species richness in Uluguru, Morogoro, Tanzania - Kacholi, David Sylvester (Tanzania Journal of Science, 2014)
This study assessed tree uses and use-values as well as impacts of human population on the forest size, species richness, basal area and stand density in the Uluguru forests in Morogoro Region. Interview with locals on the tree uses were done using structured questionnaires and use-value analysis techniques were used in analysing data. Trees with a diameter at breast height ≥ 10 cm measured at 1.3 m above the ground were sampled from a total of 114 plots of 20 m x 20 m (0.04 ha) from the seven forests. A total of 42 species belonging to 20 families were listed being useful for the local livelihoods. Of the listed species, 88% serve more than one function while 64% are used for firewood and charcoaling, 45%, and 40%, are used for timber and medicinal purposes, respectively. Milicia excelsa and Sterculia quinqueloba had highest and lowest total use-value, respectively. Ocotea usambarensis is known to treat 29% of diseases while 47% and 25% of the species with medicinal values are used to treat stomach-ache and dysentery. Roots are the most utilized tree parts for making traditional medicines, followed by barks and leaves. The human population density revealed a significant negative correlation with forest size (r = –0.90), species richness (r = –0.78), and stand density (r = –0.75). The study suggests for control of human population and their associated activities, provision of awareness on sustainable utilization of forest resources, use of alternative source of energy by locals and active involvement of the locals in management and conservation programmes